Antioxidant Effect of Phospholipids Extracted From Soyabean on Fat and Food Oil - ESHRATABADI, PARVIN; SALARVAND, ZOHREH; RASHIDI, LADAN (Asian Journal of Chemistry, 2010)
Nowdays, phospholipids are considered as a natural additive with useful and applicable effects in food industry and many studies are being carried out on this field. In this study the antioxidant effect of phospholipids extracted from 5 different soyabean varieties, named Persia (SR), Hill (HL), Williams (WZ), Gorgan 3 (GN) and Simes (SS) have been compared in soyabean oil as well as that on the stability of sunflower oil. Crude and degummed soyabean oils of all 5 varieties as well as refined sunflower seed oils with added phospholipids were subjected to induction period (IP) measurements employing Rancimat method. The results from the first step showed that Williams variety has markedly different behaviour of antioxidant in comparison with the others. Comparing the data from second step, it is concluded that Simes variety increase stability of sunflower oil more than the others.